Microbiome and Gestational Diabetes: Interactions with Pregnancy Outcome and Long-Term Infant Health - Caterina Neri; Erika Serafino; Maddalena Morlando; Alessandra Familiari (Journal of Diabetes Research)
Microbiota composition is progressively being connected to different physiologic effects, such as glucose metabolism, and also to different pathologies, such as gestational diabetes mellitus (GDM). GDM is a public health concern that affects an important percentage of pregnancies and is correlated with many adverse maternal and neonatal outcomes. An increasing number of studies are showing some connections between specific microbial composition of the gut microbiota and development of GDM and adverse outcomes in mothers and neonates. The aim of this review is to analyze the available data on microbial changes that characterize healthy pregnancies and pregnancies complicated by GDM and to understand the correlation of these changes with adverse maternal outcomes; this review will also discuss the consequences of these maternal gut microbiome alterations on neonatal microbiota composition and neonatal long-term outcomes.